Sifat Optis Tak-Linear Pada Material KDP - Setyawan, Rahmadi; Setiawati, Evi; Marhaendrajaya, Indras; Firdausi, K. Sofjan (BERKALA FISIKA, 2008)
Non-linier optical properties of transparent material Kalium Di- hydrogen Phosphate (KDP) have been identified under the influence of external magnetic fields at wavelength 632.8 nm and 532 nm by using Faraday Effect method. The external  magnetic fields used in this experiment is produced from coils with total turns of 810, wire diameter of 0,8 mm, and soft magnet core, and is flowed by maximum AC current 5 A. The magnitude of magnetic fields can be produced is 194.23 mT. The optical property measured here is rotation of polarization angle ß of the laser beam after passed the transparent material. From the experiment, it is obtained Verdet’s constant value for transparent material KDP is (12.60 ± 0.59) min/G-cm at  = 632.8 nm and (14.93 ± 0.73) min/G-cm at  = 532 nm.   Key words: non-linier optic, KDP, magnetic fields, polarization, Verdet’s constant